Milk fermentation by monocultures or co-cultures of Streptococcus thermophilus strains - Han, Mei; Wu, Yanfeng; Guo, Xiaojuan; Jiang, Lili; Wang, Xin; Gai, Zhonghui (Frontiers in Bioengineering and Biotechnology, 2022)
Direct vat-set starter cultures are the key ingredient for the production of fermented dairy products. The characteristics of the strains used for fermentation determine the fermentation time, texture and flavor of the fermented milk products. In this study, a large-scale analysis of the acid production rate, texture, carbon source utilization characteristics of Streptococcus thermophilus strains was conducted. All 100 S. thermophilus strains were divided into six groups according to the acid production rate and into two groups according to the consistency texture. A universal medium, basing on the carbon sources metabolic properties were optimized (0.5% lactose and 3.5% glucose), to culture all of the tested strains. Among them 40 strains were used to test pH-controlled conditions using this universal culture medium. After 5–7 h of fermentation, the optical density (OD) values of all fermented products exceeded 10, suggesting the potential for high-density cultivation of S. thermophilus. Although the OD could be further increased by adding more glucose, this may have hindered subsequent lyophilization because of high residual lactic acid in the fermented product. Next, the application of Streptococcus thermophilus strains in fermented milk was studied. Monocultures and co-cultures of strains were evaluated and compared. The results revealed the existence of symbiotic or competitive relationships between different S. thermophilus strains. Based on the findings, the mixing ratio of three symbiotic S. thermophilus strains was optimized. A co-culture of these three strains yielded fermented milk with high viscosity, low post-acidification, good sensory properties and processability.